(untitled)
The experiment was conducted at Dobila, Tarash of Shirajgonj in chalanbeel during the Rabi seasons of 2018-2019 and 2019-2020 to improve the existing cropping pattern, increase cropping intensity, yields and economic return through incorporating of modern crop varieties and improved management practices. The treatments were i) Mustard (var. BARISarisha-14)-Boro-Fallow cropping pattern, ii) Mustard (var. BARI Sarisha-15)- Boro-Fallow cropping pattern, iii) Mustard (var. Tori-7)-Boro-Fallow cropping patternandiv) Fallow–Boro–Fallow (existing cropping pattern). Boro rice (var. BRRI dhan29) was used to improve cropping pattern. The results revealed that the mean crop duration of improved cropping pattern ranged 192-195 days by inclusion of mustard. Rice equivalent yield of improved cropping pattern was 9.51-10.04 t ha-1 year-1 which was 46% higher than that of existing pattern (5.37 t ha-1 year-1). Land use efficiency (53%) of improved cropping pattern were 9 and 47% higher, respectively than those of existing cropping pattern. Higher mean gross return (Tk. 2,80,860 ha-1), gross margin (Tk. 169680 ha-1) and BCR (2.53) were recorded in improved cropping pattern: Mustard (var. BARI Sarisha-14)- Boro – Fallow